2014
DOI: 10.1177/1090820x14526406
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Fat Compartments in the Neck: A Cadaver Study

Abstract: This anatomic study provides a comprehensive review of fat in the neck, and the results should serve as an additional guide as surgeons approach this challenging area in surgical rejuvenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…A well‐known exception is the platysma, a superficial muscle of the anterior neck that is important for human facial mimic. In a recent study conducted with human cadavers, supraplatysmal and subplatysmal fat represented 44.7% and 30.7% of neck fat, respectively . On the other hand, as Driskell and colleagues rightly mention, two morphologically distinct layers of WAT, traditionally viewed as subdivisions of SWAT, exist below the reticular dermis in humans.…”
mentioning
confidence: 99%
“…A well‐known exception is the platysma, a superficial muscle of the anterior neck that is important for human facial mimic. In a recent study conducted with human cadavers, supraplatysmal and subplatysmal fat represented 44.7% and 30.7% of neck fat, respectively . On the other hand, as Driskell and colleagues rightly mention, two morphologically distinct layers of WAT, traditionally viewed as subdivisions of SWAT, exist below the reticular dermis in humans.…”
mentioning
confidence: 99%
“…However, the distribution of SMF was closer to 50% preplatysmal: 50% postplatysmal in 15% of their samples (n = 3/20) [17], suggesting variability among individuals. Larson et al also found variability in the distribution of SMF between the preplatysmal and postplatysmal fat compartments in their study [16]. It is worth noting that both the Renaut and Larson studies evaluated a small number of cadavers (20 and 10, respectively) [16,17].…”
Section: Introductionmentioning
confidence: 78%
“…Larson et al also found variability in the distribution of SMF between the preplatysmal and postplatysmal fat compartments in their study [16]. It is worth noting that both the Renaut and Larson studies evaluated a small number of cadavers (20 and 10, respectively) [16,17]. Therefore, it is difficult to draw conclusions about the distribution of SMF between the preplatysmal and postplatysmal fat compartments in the general population from these limited data.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations